2010
DOI: 10.1248/jhs.56.641
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced Testicular Disorders Vis-a-vis Germ Cell Apoptosis in Albino Rat: Remedial Effect of Hexane Fraction of Root of Musa paradisiaca and Leaf of Coccinia indica

Abstract: The present study was designed to investigate diabetes induced germ cell apoptosis in testis and its protection by treatment with hexane fraction of hydro-methanolic extract of root of Musa paradisiaca and leaf of Coccinia indica in composite manner. Testicular oxidative stress injury was reflected by diminution in the activities of antioxidant enzymes such as catalase, peroxidase, superoxide dismutase and glutathione-s-transferase along with elevation in levels of conjugated diene and thiobarbituric acid reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 48 publications
(46 reference statements)
3
33
0
Order By: Relevance
“…Nevertheless, Singh et al (2013) found no significant increase in testicular glutathione S-transferase levels (GST) although Raza et al (2004), Mallick et al (2010), Shah and Khan (2014), Chatterjee et al (2012Chatterjee et al ( , 2013 reported increase of GST levels in testis and/or sperm to the levels of control group. In studies by Mallick et al (2007Mallick et al ( , 2010, Hamden et al (2008), Giribabu et al (2014) and Shah and Khan (2014), the treatment with plant extracts resulted in the recovery of catalase, SOD and glutathione peroxidase (GPx) levels. Mallick et al (2007) achieved the recovery of catalase and glutathione peroxidase levels and thus antioxidant protection to the testicular tissue.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, Singh et al (2013) found no significant increase in testicular glutathione S-transferase levels (GST) although Raza et al (2004), Mallick et al (2010), Shah and Khan (2014), Chatterjee et al (2012Chatterjee et al ( , 2013 reported increase of GST levels in testis and/or sperm to the levels of control group. In studies by Mallick et al (2007Mallick et al ( , 2010, Hamden et al (2008), Giribabu et al (2014) and Shah and Khan (2014), the treatment with plant extracts resulted in the recovery of catalase, SOD and glutathione peroxidase (GPx) levels. Mallick et al (2007) achieved the recovery of catalase and glutathione peroxidase levels and thus antioxidant protection to the testicular tissue.…”
Section: Resultsmentioning
confidence: 90%
“…In 31.6% of studies that evaluated the blood insulin concentration, Mallick et al (2010) obtained the most efficient results, restoring the low levels observed in diabetic animals to those of control group. However, Mallick et al (2007), Chatterjee et al (2012Chatterjee et al ( , 2013, Hajizadeh et al (2014) and Shah and Khan (2014) reported a recovery compared to untreated diabetic animals.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…[21][22][23][24] UV-Visible spectroscopy: Determination of λ max UV-Visible spectra (for λ max) were recorded using PerkinElmer Lambda 35 UV/VIS dual beam spectrophotometer fitted with quartz cells. Both U 1 and U 2 were separately dissolved in and diluted with HPLC grade methanol to prepare the solutions of 25µg/mL and the compounds were scanned over entire UV range (400-199 nm) for recording of UV spectra to determine the λ max of the compounds.…”
Section: Phytochemical Analysismentioning
confidence: 99%